2018
DOI: 10.3748/wjg.v24.i27.3013
|View full text |Cite
|
Sign up to set email alerts
|

Liver intravoxel incoherent motion diffusion-weighted imaging for the assessment of hepatic steatosis and fibrosis in children

Abstract: AIMTo evaluate the correlation between intravoxel incoherent motion (IVIM) diffusion-weighted imaging (DWI) parameters and the degree of hepatic steatosis and fibrosis in children.METHODSThis retrospective study was approved by the institutional review board. The children (≤ 18 years) who underwent liver IVIM DWI with 8 b-values under the suspicion of hepatic steatosis or fibrosis from February 2013 to November 2016 were included. Subjects were divided into normal, fatty liver (FAT), and fibrotic liver (FIB) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…França et al 5 reported that their subjects without steatosis had a median PF of 0.28, while their subjects with steatosis had a median PF of 0.35 or more. Observations of positive correlation between liver steatosis and PF have also been reported by other authors, such as Shin et al 6 It has been well established that liver steatosis induces D slow reduction. [7][8][9][10][11] The presence of fat may decrease the diffusion coefficient of water in tissue by restricting the diffusion of water within hepatocytes.…”
Section: Observed Paradoxical Perfusion Fraction Elevation In Steatotsupporting
confidence: 76%
See 1 more Smart Citation
“…França et al 5 reported that their subjects without steatosis had a median PF of 0.28, while their subjects with steatosis had a median PF of 0.35 or more. Observations of positive correlation between liver steatosis and PF have also been reported by other authors, such as Shin et al 6 It has been well established that liver steatosis induces D slow reduction. [7][8][9][10][11] The presence of fat may decrease the diffusion coefficient of water in tissue by restricting the diffusion of water within hepatocytes.…”
Section: Observed Paradoxical Perfusion Fraction Elevation In Steatotsupporting
confidence: 76%
“…15 Metabolically, hepatic fat accumulates negligible 18 F-fluorodeoxyglucose (FDG). 16 Thus, PF in the literature noted above [2][3][4][5][6][7][8][9][10][11] was likely artificially promoted by IVIM modeling due to an actually decreased D slow . Note that, in cases when the livers with steatosis had been contaminated with steatohepatitis pathology, it has been established that steatohepatitis decreases, instead of increases, PF.…”
Section: Observed Paradoxical Perfusion Fraction Elevation In Steatotmentioning
confidence: 96%
“…BEM studies in adults with liver cirrhosis showed that either D* or f was significantly lower in cirrhotic livers than in healthy livers, while D showed frequent trends for no significant difference or poor correlation with fibrosis level [18,19]. One recent study on pediatric liver BEM, D*, and f values were significantly decreased in liver fibrosis [20]. We can suggest that decreased values in perfusion related parameters of BA patients could be from portal hypertension and decreased portal perfusion from increased collagen fibers and activated stellate cells in fibrotic livers [19].…”
Section: Discussionmentioning
confidence: 99%
“…We can suggest that decreased values in perfusion related parameters of BA patients could be from portal hypertension and decreased portal perfusion from increased collagen fibers and activated stellate cells in fibrotic livers [19]. Decreased microperfusion parameters from BEM were also noted in BA patients after receiving Kasai operation [20]. However, BA was known to have hepatic arteriopathy and increased hepatic arterial flow on color Doppler US could be used for the diagnosis of BA [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, liver ADC values in biliary atresia patients were lower than those in a control group and had a negative correlation with the degree of liver fibrosis following Kasai operation (6162). On IVIM assessments, hepatic D * values were lower than those in normal children and showed negative correlation with increased liver stiffness (63). Figure 3 shows the utility of mon-, bi-, and stretched exponential models in the liver of a biliary atresia patient.…”
Section: Clinical Applications Of Quantitative Hepatobiliary Imagingmentioning
confidence: 99%